90=m(m+46)

Simple and best practice solution for 90=m(m+46) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=m(m+46) equation:



90=m(m+46)
We move all terms to the left:
90-(m(m+46))=0
We calculate terms in parentheses: -(m(m+46)), so:
m(m+46)
We multiply parentheses
m^2+46m
Back to the equation:
-(m^2+46m)
We get rid of parentheses
-m^2-46m+90=0
We add all the numbers together, and all the variables
-1m^2-46m+90=0
a = -1; b = -46; c = +90;
Δ = b2-4ac
Δ = -462-4·(-1)·90
Δ = 2476
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{2476}=\sqrt{4*619}=\sqrt{4}*\sqrt{619}=2\sqrt{619}$
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-46)-2\sqrt{619}}{2*-1}=\frac{46-2\sqrt{619}}{-2} $
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-46)+2\sqrt{619}}{2*-1}=\frac{46+2\sqrt{619}}{-2} $

See similar equations:

| 5-3x/2=2 | | 12x-3x-5x=0 | | 10p+8=12p-5 | | 3.9t-9.6t=-25.3 | | y/5=-18 | | 5(2x-8)+15=-15. | | 2/3*t=8/9 | | 3*(-5x+3)=-14*(x+1) | | -2x+5+6x+1=-2x+6x+10 | | 7x-3-6x=5+22 | | 7x-3-6x=24+3 | | 4z/7-9=7 | | (-3x)-4=2x-14 | | x/9-8=0 | | 3(x+2)2=15 | | x=3x+5-(2x-9) | | 3(x-5)+7=0 | | -x+13=-27 | | 2x–7=3x+2 | | 5n-9=43 | | 16(7)=14x(8x) | | x-10+4x-25+x-5=180 | | 8x+2=6x-1+7x+7 | | 11x−24=3x | | 7x+3/2=4x-5/3 | | 8^(2x-1)=35^x | | 8^2x-1=35^x | | 7x^2+18x=193 | | 3(5x-3)=2x-35 | | 7x-1=3x+47 | | 0.08t+0.11(100-t)=9.8 | | 5.6=3.2x+13.2 |

Equations solver categories